THE DIALECTIC OF POSITIVISM AND SUBSTANTIVE JUSTICE: THE PANCASILA RULE OF LAW PARADIGM - Elviandri; Muhammad Amin; Demitha selvira amellia; Ricky Indrawan safutra; Andi Wibowo (Cattleya Darmaya Fortuna, 2025)
This study examines the dialectic between legal positivism and substantive justice within the framework of the Pancasila legal state paradigm as an effort to find a balance between legal certainty and substantive justice. The background of this study stems from the hegemony of legal positivism in Indonesia, which emphasizes formal and procedural legality, often neglecting the aspect of substantive justice that is at the core of the Pancasila legal ideal. In practice, law tends to stop at normative certainty (law in books), without touching on the values of humanity and justice that exist in society (law in action). The urgency of this study lies in the need to reposition Pancasila as a grundnorm and ethical foundation to return the orientation of Indonesian law to substantive justice, not merely formal justice. The research method used is juridical-normative with a legal philosophy and conceptual hermeneutics approach, which interprets law as das sollen (what should be). The results of the study show that rigid legal positivism has created a gap between legal certainty and substantive justice. The Pancasila legal paradigm presents itself as an integrative model that unites legal certainty and moral justice, positioning law not merely as an instrument of power, but as an ethical and spiritual means to uphold civilized justice. Thus, the Pancasila legal state offers a philosophical foundation for harmonizing positive norms and substantive values of justice in the national legal system.